(3cJGH GdCeQ HGdeYQha hGdfgi Yf GdefcQs - (3YHO Gddg Hf eMeO Hf YHjO Hf SajGf Hf bjS, CHh HcQ, GHf CHj GdOfjG GdbQTj , J (B281 (3g` s
(3ChdgG (B:s
(3Yf bjS Hf CHj MGRe bGd bQCf CHh HcQ gPg GdBjI (B:" (3jG CjgG GdPjf BefhG Ydjce CfaSce dGjVQce ef Vd EPG EgJOjJe (B" (3Ke bGd Ef GdfGS jVYhf gPg GdGjI Ydi ZjQ ehVYgG s
(3BNQgG (B:s
(3Efi cfJ CeQ HGdeYQha hdG CYed Hg hGfgGg Yf GdefcQ hGYed Hg ef cJGH GdGeQ HGdeYQha hGdfgi Yf GdefcQ hGdMeO ddg hMOg s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B118 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B131s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JQeje s
Keywords: (3GdJUha hGdBOGH GdTQYjIs